1995
DOI: 10.1016/0736-5748(95)00080-1
|View full text |Cite
|
Sign up to set email alerts
|

Pentobarbital modulatory effect on GABA binding sites in developing chick optic lobe

Abstract: Barbiturates are allosteric modulators of the CNS GABAA receptor, increasing [3H]-GABA binding to its receptor sites. In the present work we have studied the modulatory effect of the barbiturate pentobarbital on low-affinity GABA binding sites during ontogenetic development of the chick optic lobe. Our results indicate that [3H]-GABA binding enhancement by pentobarbital shows a differential profile during development, following a two-component enhancement model at early stages of development and a single-compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 35 publications
(22 reference statements)
0
4
0
Order By: Relevance
“…Binding experiments carried out in our laboratory have demonstrated that both the BZ type I and type II are already expressed during development but with different temporal patterns. BZ type II binding sites are detected earlier than is the BZ type I (Gravielle and Fiszer de Plazas, 1995). These binding results are probably due to the changes in α 1 and α 2 expression described herein.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Binding experiments carried out in our laboratory have demonstrated that both the BZ type I and type II are already expressed during development but with different temporal patterns. BZ type II binding sites are detected earlier than is the BZ type I (Gravielle and Fiszer de Plazas, 1995). These binding results are probably due to the changes in α 1 and α 2 expression described herein.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the spatial pattern of expression, i.e., the distribution in the different layers during development, remains unknown. Differences in pharmacologic and biochemical properties of this receptor observed during normal development (Fiszer de Plazas et al, 1995; Pignataro et al, 1996; Viapiano and Fiszer de Plazas, 1998) or after injury at different embryonic days (Rodríguez Gil et al, 2000, 2002) could be attributed to changes in the subunit expression pattern.…”
mentioning
confidence: 99%
“…In previous studies, we investigated the modulatory action of benzodiazepines, barbiturates, and neurosteroids on the GABA A receptor complex during chick optic lobe development by means of GABA and benzodiazepine binding and GABA-dependent chloride uptake experiments (Fiszer de Plazas and Mitridate de Novara, 1990;Fiszer de Plazas et al, 1995;Pignataro et al, 1996;Viapiano and Fiszer de Plazas, 1998;Gravielle et al, 1998). As in the case of zinc, all modulators analyzed act in an age-dependent manner, disclosing their maximal effects at early developmental stages and indicating a change in GABA A receptor sensitivity to these drugs during development.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies from our laboratory have established the pattern of expression, heterogeneity, modulation properties, and functionality of the GABA A R complex in the developing chick OT (Fiszer de Plazas and Mitridate de Novara, 1990; Fiszer de Plazas et al, 1995; Gravielle et al, 1998; Viapiano et al, 1998). We have also characterized the time of appearance and the temporal evolution of high‐ and low‐affinity GABA binding sites (Fiszer de Plazas et al, 1993).…”
mentioning
confidence: 99%